2019
DOI: 10.1002/1873-3468.13338
|View full text |Cite
|
Sign up to set email alerts
|

Genes of the undead: hibernation and death display different gene profiles

Abstract: A degree of regulation continues into death according to post‐mortem transcriptome studies, which have identified ‘zombie genes’ that come alive hours and days after organismal death. We hypothesized that hibernation, representing the closest natural mammalian phenomenon to death, would display similar gene expression profiles. Exploring zombie genes using qPCR and available transcriptomic resources from multiple torpid tissues in 13‐lined ground squirrels showed little in common with gene profiles observed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Therefore, while we studied the effect of simulated PMI at room temperature, in most cases following death the brain will be at a much higher temperature for a longer period than we used in our study here and therefore would likely have more rapid changes. While some studies have suggested that the RNA transcriptome is stable up to 30 h after death 23,30 , dynamic changes in RNA levels for specific cell types described here as a result of the PMI have been reported by others showing RNA degradation 31 , chromatin modification 6 , activation of gene expression [32][33][34] , and protein degradation 22 . While we did not directly look at protein expression, the predicted cell differences implicating specific cell populations would likely create corresponding proteomic changes in glia and neuronal cell populations.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, while we studied the effect of simulated PMI at room temperature, in most cases following death the brain will be at a much higher temperature for a longer period than we used in our study here and therefore would likely have more rapid changes. While some studies have suggested that the RNA transcriptome is stable up to 30 h after death 23,30 , dynamic changes in RNA levels for specific cell types described here as a result of the PMI have been reported by others showing RNA degradation 31 , chromatin modification 6 , activation of gene expression [32][33][34] , and protein degradation 22 . While we did not directly look at protein expression, the predicted cell differences implicating specific cell populations would likely create corresponding proteomic changes in glia and neuronal cell populations.…”
Section: Discussionmentioning
confidence: 57%
“…In fact, some biomolecules (e.g., caspases) can be activated even during the post-mortem period, showing that death is a dynamic process 5 . RNA degradation and synthesis after death has been investigated in the past 2 , 3 , 6 . However, most of the available data refer to studies that aimed to unravel molecular mechanisms of mental disorders, such as schizophrenia, Alzheimer and drug addiction 7 9 and little is known about how these processes occur in healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely assumed that death rapidly causes a complete shutdown of all molecular activities including transcription, translation, protein modifications and signalling cascades. This is definitely not the case [ 2 , 3 , 4 , 5 ], however, with the post-mortem proteome representing an intriguing map of the potential of a biological system. In living organisms, the decommissioning of cells occurs due to precisely expressed genetic and epigenetic controls that reduce the risk of the accumulation of damaged cells [ 6 ].…”
Section: Introductionmentioning
confidence: 99%